Midnights Meant for Magic Frederick Ashton, Michael Corder and Cinderella - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Ashton, Corder and Cinderella. Ashton had a blank page to work on; Corder had to overwrite his own and his audience's memories. PALABRAS CLAVE: Royal Ballet, English National Ballet, Cinderella, Frederick Ashton, Michael Corder.